IS KAZAKHSTAN IMMUNE TO COLOR REVOLUTIONS? THE SOCIAL MOVEMENTS PERSPECTIVE. - NURSEIT NIYAZBEKOV (Demokratizatsiya)
A quarter-century of independence has transformed Kazakhstan into a leading Central Asian economy and consolidated authoritarian regime. The political systems of Ukraine, Georgia, and Kyrgyzstan were very similar to that of Kazakhstan until they were hit by a "color revolution virus" that dismantled authoritarian institutions and initiated democratic reforms. How, then, has Kazakhstan--like other Central Asian autocracies-- remained somewhat immune to these bottom-up revolutions? This paper adopts a social movement perspective to explain how such factors as resource mobilization, political opportunities, and protest framing strategies have shaped protest mobilization dynamics in Kazakhstan, a variable that was crucial to the success of color revolutions. Through elite interviews and newspaper content analysis of protest events in Kazakhstan between 1992 and 2009, the article suggests that the Kazakh government has erected numerous anti-democratic barriers, illustrating how autocracies have learned from the successes and failures of color revolutions to remain in power.